THROUGH THE METAPHORICAL LENS: UNDERSTANDING OTHERING OF LANGUAGE LECTURERS IN INDONESIAN HIGHER EDUCATION - Yusri Yusuf; Jarjani Usman; Yunisrina Qismullah Yusuf (English Review: Journal of English Education, 2022)
This research attempted to delve into the Indonesian and English lecturers’ views on othering experiences through the metaphorical lens. The data collection employed interviews with ten lecturers teaching at two public universities in Aceh, Indonesia. The interviews were recorded and transcribed, and further analyzed using Johnson and Lakoff’s Conceptual Metaphor Theory (CMT) where a metaphor is referred to understanding and experiencing one kind of thing in terms of another thing. The results revealed that the lecturers expressed their feelings of being othered through 14 Acehnese metaphorical expressions. They are ‘awak dalam’, ‘awak droe’ ‘asoe lhôk’, ‘Cina saboh geudông’, and ‘ureung lhap darah’,‘kön ureung gulam budée’, ‘kön awak dalam’, ‘kön awak droe jih’, ‘kön syara Ma jih’, ‘gob mat aweuk’, ‘ureung di luwa pageu’, ‘jamok di luwa keuleumbu’, ‘awak gop’, and ‘awak blah déh laôt’. Those in power (i.e., the ‘us’) discriminated against some lecturers (i.e., the ‘them’) by not providing them equal opportunities in the institution, regardless of their quality and credentials. Othering that existed in the universities negatively affected their work enthusiasm, education quality, social justice, and equality. Consequently, othering must be eradicated so that the human resources recruitment and education in universities uphold the principles of transparency, equality, and accountability.